Impact of Automation, Workforce Training, and Lean Manufacturing on Production Efficiency in the Indonesian Automotive Industry (West Science Interdisciplinary Studies, 2025)
This study will explain how automation, workforce training, and lean manufacturing influence production efficiency within the Indonesian automotive industry. Data were collected from 76 respondents and analyzed using SPSS version 26, applying a quantitative research approach. It was observed that all three factors enhance production efficiency significantly, in the order of workforce training, automation, and lean manufacturing. These results highlight how integrating technology, human resource development, and process optimization will provide sustainable efficiency improvements. These findings suggest some actionable steps that industry players may take in their efforts to improve competitiveness within the turbulent market environment.